Interpretable Job Recommendation from Multiple Sources of Occupational Evidence: Early Results - Tokuda, Eric Keiji; Delbem, Alexandre Cláudio Botazzo; Soares, Anderson da Silva (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
Skill-based occupation recommenders should show how evidence from different data sources leads to ranked occupations, especially for job seekers with limited literacy or access to guidance. This paper presents a deterministic pipeline for traceable job recommendation that integrates structured occupational descriptors with annotated job-text spans and converts them into yes/no questionnaire evidence. The pipeline builds O*NET occupation profiles, audits SkillSpan skill and knowledge spans, maps them to occupational descriptors, generates traceable questions, links questions back to occupations, and tests whether simulated answers recover the source occupation. The question structure works well under controlled reconstruction: compact task-based questions recover occupations almost perfectly. The multi-source text-integration branch is weaker: lexical extraction predicts 9,375 spans for 2,264 gold spans, and conservative normalization accepts only 662 mappings. The pipeline is therefore a job-recommendation prototype and audit layer for inclusive occupational evidence, showing where evidence remains usable and where extraction or mapping breaks down.